Automation, Operation and Maintenance of Control and Communication Systems - Szymak, Piotr; Hożyń, Stanisław; Piskur, Paweł (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue constitutes the collection of the selected papers, which results were presented during the XVIII Conference on Automation, Operation and Maintenance of Control and Communication Systems ASMOR 2022. The conference took place in Władysławowo (Poland) on 12-14 October 2022. The scope of the conference was mainly focused on automation and exploitation aspects of the control and communications systems. In order to meet the highest quality standards for published papers, only the articles selected by the ASMOR Scientific Committee and the Electronics Editors were qualified for an extensive reviewing process.